PHYSICAL FITNESS DEVELOPMENT AND TRAINING PROGRAM FOR MEMBERS OF INDONESIAN NATIONAL ARMY (AN EVALUATION STUDY IN MILITARY REGIONAL COMMAND IV/DIPONEGORO) - Mulyono, Mulyono; Setijono, Hari; Rahayu, Setya (Universitas Negeri Semarang, 2017)
This study is intended to describe the implementation of the physical fitness development and training program for members of MRC (Military Regional Command) IV/Diponegoro by evaluating CIPP (context, input, process and product). A qualitattve method was used. The data were collected by using questionnaires, observation, interviews and documents. The respondentsts include Comand-in-chief, trainers, army members, program, facilities, infrastructure and documents. The data were analyzed by using non statistic qualitative analysis. The results of the study show that the context is evaluated to be very good by 86.67% of the respondentsts and good by 13.3% of them. The input is evaluated to be very good by 33.33% of the respondentsts and good by 66.67% of them. The process is evaluated to be very good by 66.67% of the respondentsts and good by 56.67% of them. The product is evaluated to be very good by 36.67% of the respondentsts and good by 63.33% of them. It is concluded that the evaluation study is of good quality and to be very good, some improvement on input and process should be made.